Facile Synthesis of Polysubstituted 2-Pyrones via TfOH-Mediated Ring Expansion of 2-Acylcyclopropane-1-carboxylates - Shao, Jiru; An, Caiyun; Wang, Sunewang R. (Synthesis, 2021)
A facile route to polysubstituted 2-pyrones from readily available 2-acylcyclopropane-1-aryl-1-carboxylates mediated by TfOH is reported. The strongly donating 1-aryl group is important for directing the C–C bond cleavage of the donor-acceptor cyclopropane ring, which then leads to the formation of the 2-pyrone ring through lactonization.
Keywords: carbocycles; heterocycles; ring expansion; Brønsted acid; synthetic methods; cyclopropanes; 2-pyrones